CT maxillary sinus evaluation-A retrospective cohort study - Guerra-Pereira, Ines (2015)
Background: Proximity of the dental roots to the sinus floor makes dental disease a probable cause of maxillary sinusitis. The aim of this study was to find out if maxillary sinus pathologic changes were more prevalent in patients with dental disease and to evaluate the performance of computed tomography (CT) in analyzing and detecting apical periodontitis and other odontogenic causes on the maxillary sinusitis etiology in a Portuguese Caucasian population.Material and Methods: Retrospective cohort study. The total sample of 504 patients and their CT was included in this study. The patients were from a private dental clinic, specializing in oral surgery, where the first complaint was not directly related to sinus disease, but with dental pathology. For each patient, the etiological factors of maxillary sinusitis and the imaging CT findings were analyzed. All the axial, coronal and sagittal CT slices were evaluated and general data were registered. The latter was selected based on the maxillary sinus CT published literature.Results: 32.40% of patients presented normal sinus (without any etiological factor associated), 29.00% showed presence of etiological and imaging findings in the maxillary sinus, 20.60% had only imaging changes in the maxillary sinus and 18.00% of patients presented only etiological factors and no change in the maxillary sinus.Conclusions: Radiological imaging is an important tool for establishing the diagnosis of maxillary sinus pathology. These results indicate that the CT scan should be an excellent tool for complement the odontogenic sinusitis diagnosis.